Some operations on type-2 intuitionistic fuzzy sets. - Cường, Bùi Công; Anh, Tống Hòang; Hải, Bùi Dương (Journal of Computer Science and Cybernetics, 2012)
In the last decades, there have been some extensions of fuzzy sets and their applications.Recently, type-2 fuzzy set and intuitionistic fuzzy set are two of them, drawing a great deal ofscientist's attention because of their widespread range of applications. In this paper, we introduce anew concept - type-2 intuitionistic fuzzy set and propose some properties of their operations.